Structural and Epistemological Obstacles to a Moderate Qur’anic Interpretive Discourse: A Methodological Analysis - Muhammad Yusuf al-Deek (Universiti Sains Islam Malaysia, 2026)
Maʿālim Al-Qurʾān Wa Al-Sunnah, Volume 21 Issue 2 Page (209–233)